Breast Tumor Angiogenesis and Tumor-AssociatedMacrophages: Histopathologist’s Perspective - Ewe, Seng Ch’ng; Jaafar, Hasnan; Tuan Sharif, Sharifah Emilia (Hindawi Publishing Corporation, 2011)
Much progress has been made since the conceptualization of tumor angiogenesis—the induction of growth of new blood vessels by tumor—as a salient feature of clinically significant primary or metastatic cancers. From a practicing histopathologist’s point of view, we appraise the application of this concept in breast cancer with particular reference to the evaluation of proangiogenic factors and the assessment of new microvessels in histopathological examination. Recently, much focus has also been centered on the active roles played by tumor-associated macrophages in relation to tumor angiogenesis. We review the literature; many data supporting this facet of tumor angiogenesis were derived from the breast cancer models. We scrutinize the large body of clinical evidence exploring the link between the tumor-associated macrophages and breast tumor angiogenesis and discuss particularly the methodology and limitations of incorporating such an assessment in histopathological examination.